Clinical Profile and Immunocompromising Conditions among Newly Diagnosed Tuberculosis Patients: A Prospective Observational Study - Niraj Bam; Bibek Shrestha; Amrit Pandey; Bikash Mishra (Nepal Journal of Public Health, 2026)
Background: In low and middle-income countries, TB continues to be a significant public health challenge. Active disease, atypical presentation, delayed diagnosis and poor outcomes are more common in immunocompromised patients; however, information on the clinical profile of these patients is limited in Nepal. The objectives of this study are to describe the clinical presentation, profile and immunocompromising status of newly diagnosed tuberculosis patients and to compare the selected clinical features of immunocompromised patients with non-immunocompromised patients. Methods: This is a prospective observational study was conducted from June 2025 to April 2026. 160 newly diagnosed patients of pulmonary tuberculosis, extrapulmonary tuberculosis or both were enrolled consecutively. Results: Among 160 patients, 85 (53.1%) were male and 94 (58.8%) were from urban areas. The age group of greater than 60 years was the most common (32.5%). The major type of TB was pulmonary (76.9%) then extrapulmonary (20.0%) and combined (3.1%). Cough was the most frequent symptom (68.8%), followed by fever (63.7%), weight loss (62.5%), night sweats (53.8%) and loss of appetite (53.1%). In total, there were 102 (63.7%) immunocompromised patients. The most prevalent immunocompromise condition was diabetes mellitus (13.1%), severe malnutrition (8.8%) and chronic liver disease (6.9%). Immunocompromised patients were much more likely to have a fever and night sweats. Conclusion: Most of the newly diagnosed tuberculosis patients had immunocompromising status, especially diabetes mellitus, malnutrition and chronic liver disease. There was significant association between fever and night sweats with immunocompromised status, thus routine evaluation of underlying immune-impairing diseases in the care of tuberculosis is warranted.